Role of protein Post-translational modifications in enterovirus infection - Zhao, Xiaohui; Hu, Yibo; Zhao, Jun; Liu, Yan; Ma, Xueman; Chen, Hongru; Xing, Yonghua (Frontiers in Microbiology, 2024)
are the main cause of a number of neurological diseases. Growing evidence has revealed that successful infection with enteroviruses is highly dependent on the host machinery, therefore, host proteins play a pivotal role in viral infections. Both host and viral proteins can undergo post-translational modification (PTM) which can regulate protein activity, stability, solubility and interactions with other proteins ; thereby influencing various biological processes, including cell metabolism, metabolic, signaling pathways, cell death, and cancer development. During viral infection, both host and viral proteins regulate the viral life cycle through various PTMs and different mechanisms, including the regulation of host cell entry, viral protein synthesis, genome replication, and the antiviral immune response. Therefore, protein PTMs play important roles in EV infections. Here, we review the role of various host-and virus-associated PTMs during enterovirus infection.